Comparative genomics reveals dynamic genome evolution in host specialist ectomycorrhizal fungi. Issue 2 (6th February 2021) - Lofgren, Lotus A.; Nguyen, Nhu H.; Vilgalys, Rytas; Ruytinx, Joske; Liao, Hui‐Ling; Branco, Sara; Kuo, Alan; LaButti, Kurt; Lipzen, Anna; Andreopoulos, William; Pangilinan, Jasmyn; Riley, Robert; et al.
Summary: While there has been significant progress characterizing the 'symbiotic toolkit' of ectomycorrhizal (ECM) fungi, how host specificity may be encoded into ECM fungal genomes remains poorly understood. We conducted a comparative genomic analysis of ECM fungal host specialists and generalists, focusing on the specialist genus Suillus . Global analyses of genome dynamics across 46 species were assessed, along with targeted analyses of three classes of molecules previously identified as important determinants of host specificity: small secreted proteins (SSPs), secondary metabolites (SMs) and G‐protein coupled receptors (GPCRs). Relative to other ECM fungi, including other host specialists, Suillus had highly dynamic genomes including numerous rapidly evolving gene families and many domain expansions and contractions. Targeted analyses supported a role for SMs but not SSPs or GPCRs in Suillus host specificity. Phylogenomic‐based ancestral state reconstruction identified Larix as the ancestral host of Suillus, with multiple independent switches between white and red pine hosts. These results suggest that like other defining characteristics of the ECM lifestyle, host specificity is a dynamic process at the genome level. In the case of Suillus, both SMs and pathways involved in the deactivation of reactive oxygen species appear to be strongly associated with enhanced host specificity.